Livestock Breeds And Breeding Practices In Himachal Pradesh (India) - Thakur, D.; Sharma, A.K.; Katoch , S. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
The present study was undertaken to evaluate the livestock species, breed composition and breeding practices followed in high altitude regions of Himachal Pradesh, India. Investigations were carried out in 4-5 cluster villages of three blocks of Chamba district through personal interviews of 180 respondents. High proportion of households reared different livestock species (81.12 per cent cows, 66.12 per cent bulls, 27.78 per cent buffaloes and 36.67 per cent sheep and Goat) in the region .Livestock breeding practices in the form of natural service and Artificial Insemination(AI), were followed by livestock owners. In cows, AI was preferred whereas in Buffaloes natural service was preferred. Constraints affecting AI services were poor conception rate, poor accessibility of AI, higher input requirement for progeny and less awareness about AI .On the other hand, poor progeny and non availability of superior germ plasm were the major constraints associated with natural service in the region.